Comment on “While the Laparoscopic Appendectomy Is the Gold Standard in the Treatment of Acute Appendicitis, What Should Be the Preference for Closure of the Appendix Stump?” - Betul Guzelyuz (Düzce Tıp Fakültesi Dergisi)
Comment on “While the Laparoscopic Appendectomy Is the Gold Standard in the Treatment of Acute Appendicitis, What Should Be the Preference for Closure of the Appendix Stump?”